ARTROPODOS ASOCIADOS AL MATORRAL COSTERO: ACARE ORIBATIDA - Covarrubias, Rene (Acta Entomológica Chilena, 2022)
An analysis is done of the Cryptostigmatid mites (Oribatida, Acariña) in the Coastal Steppe, Chile. An annual cycle of samples was carried on separately from 10 different local situations, mainly the dominant species of vegetation. The Criptostigmata are analyzed actually as a guild, or group; their densities show significanl differences, either for time or substrate factors, interactions being also significant, after a two way analysis of variance. The question whether the densities of the Oribatid guild, are or not typical under the different substrates for a given month, was tried by means of an analysis of the hierarchies of the densities, applying a rank correlation. The answer is that in most cases (70%) the density of the guild is typical, that is, sensible as a group variable, to ecológica! factors described. The study is completed with a soil Chemical typification.